Life Cycle Assessment of microtubular solid oxide fuel cell based auxiliary power unit systems for recreational vehicles. (1st November 2017) - Benveniste, Gabriela; Pucciarelli, Martina; Torrell, Marc; Kendall, Michaela; Tarancón, Albert
Abstract: This paper investigates the potential environmental impacts of an auxiliary power unit (APU) system, based on microtubular solid oxide fuel cell (mSOFC) fed by liquefied propane gas (LPG), built to provide energy to the leisure battery of a recreational vehicle (RV). In addition, a comparison between the proposed APU system and a conventional system is presented. The work presents an analysis of the different environmental impacts regarding the proposed design and manufacturing method. The Life Cycle Assessment (LCA) methodology following ISO 14040-44.approach has been adopted for the analysis as it enables a holistic view of the environmental behaviour of the studied system. LCA is a methodology to assess each and every impact associated along the whole value chain of a process or product. This assessment based on the entire life cycle of the system, from the raw materials production to the final disposal has been performed. For this purpose, an extensive data collection focusing on resources consumption (energy and materials) and emissions has been executed to ensure that all the life cycle stages are properly characterized. The results disclose that the production of the APU system is the main source of the environmental impacts. Specifically, for Global Warming Potential (GWP) indicator, the production phase contributes to 54% to the overall value for this impact category. Detailed comparative analysis of different fabrication approaches reveal that the environmental impact can be minimised and is diminish in any case when compared to conventional APU systems (reduction of 45% CO2 equivalent emissions and 88% Primary Energy consumption compared to conventional Diesel APU systems) Results highlighted that the replacement of silver wires by the lanthanum chromium material could reduce significantly the non-fossil Abiotic Depletion Potential impact (88% reduction) and the Marine Toxicity Potential impact (18% reduction). For cutting down the GWP and the primary energy impacts it should be applied a global reduction of the energy consumed in the manufacturing and an improving in the system efficiency. Highlights: Life cycle assessment of APU system based on microtubular SOFC. Scenarios analysis for improving the design. Overall environmental impacts of the mSOFC system show up that its production stage has the highest outputs. Reduction of 45% CO2 equivalent emissions and 88% Primary Energy consumption compared to conventional Diesel APU systems. Replacement of Ag wires by the La-Cr material may reduce the ADP-elements by 88% and the MAETP impacts (18%).